“Don't eat that, you'll get fat!” Exploring how parents and children conceptualise and frame messages about the causes and consequences of obesity - Thomas, S.; Olds, T.; Pettigrew, Simone; Randle, M.; Lewis, S. (Pergamon, 2014)
Family interactions about weight and health take place against the backdrop of the wider social discourse relating to the obesity epidemic. Parents (and children) negotiate complex and often contradictory messages in constructing a set of beliefs and practices around obesity andweight management. Despite this, very little research attention has been given to the nature of family-unit discourse on the subject of bodyweight and it's potential influence on the weight-related behaviours of family members. This includes the broad influence that dominant socio-cultural discourses have on family conceptualisations of weight and health. Using indepth qualitative interviews with 150 family ‘groups’ comprised of at least one parent and one child in Victoria and South Australia, we explored how parents and children conceptualise and discuss issues of weight- and health-related lifestyle behaviours. Data were analysed using Attride-Stirling's (2001) thematic network approach. Three thematic clusters emerged from the analysis. First, both parents and children perceived that weight was the primary indicator of health. However, parents focused on the negative physical implications of overweight while children focused on the negative social implications. Second, weight and lifestyle choices were highly moralised. Parents saw it as their responsibility to communicate to children the ‘dangers’ of fatness. Children reported that parents typically used negatively-framed messages and scare tactics rather than positively-framed messages to encourage healthy behaviours. Third was the perception among parents and children that if you were thin, then eating habits and exercise were less important, and that activity could provide an antidote to food choices.Results suggest that both parents and children are internalising messages relating to obesity and weight management that focus on personal responsibility and blame attribution. These views reflect the broader societal discourse, and their consolidation at the family level is likely to increase their potency and make them resistant to change.